Pengaruh Environmental Performance dan Environmental Disclosure Terhadap Financial Performance: Studi Kasus Perusahaan Industri dan Bahan Dasar Kimia pada Bursa Efek Indonesia Tahun 2019 – 2022 - Fatharani Az-Zahra; Yanti; Fista A Sunjaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of the research is to determine the influence of environmental performance and environmental disclosure on financial performance. The research method used is a quantitative approach. The data used comes from annual reports of industrial and basic chemical companies which are listed on the Indonesia Stock Exchange (BEI), as well as PROPER reports which are published by the Ministry of the Environment (KLH). The sampling technique was carried out using purposive sampling. Data analysis was carried out using the SmartPLS version 3.0 application through hypothesis testing, outer model and inner model. The research results show that environmental performance has a significant influence on the company's financial performance, while environmental disclosure does not have a significant influence on the company's financial performance. This conclusion is based on the idea that businesses that have good environmental performance will be well received by investors and other stakeholders, which will ultimately have an impact on financial performance. Apart from that, it was revealed that a company's Financial Performance is not only assessed based on the Environmental Disclosure disclosed by the company, but also through the company's overall revenue or profits. It is also hoped that the company sample will be taken into greater consideration so that the research can produce a more comprehensive understanding of the impact of Environmental Disclosure and Environmental Performance on other sectors.